The impact of outpatient clinical teaching on students' academic performance in obstetrics and gynecology - Bahaeldin A Hassan; Omer A Elfaki; Muhammed A Khan (Wolters Kluwer Medknow Publications, 2017)
INTRODUCTION: Clinical teaching at outpatient settings is an essential part of undergraduate medical students' training. The increasing number of students in many medical schools and short hospital stays makes inpatient teaching alone insufficient to provide students with the required clinical skills. To make up this shortfall, outpatient clinical teaching has been implemented by our Department of Obstetrics and Gynecology, King Khalid University, KSA, throughout the academic year 2015-2016. The aim of this study was to evaluate the impact of clinical teaching at outpatient settings on the academic performance of our students. MATERIALS AND METHODS: In this comparative retrospective study, the effects of outpatient clinical teaching of obstetrics and gynecology on the academic performance of student was assessed through an objective structured clinical examination (OSCE). During their course on obstetrics and gynecology, 58 students had their clinical teaching both at inpatient and outpatient settings and constituted "study group". The remaining 52 students had clinical teaching only at inpatient settings and were considered "control group". Students in both groups sat for OSCE at the end of week 8 of the gynecology course. Students in both groups sat for OSCE at the end of week 8 of the gynecology course. Four stations were used for assessment: obstetric history, gynecological history, obstetric physical examination of pregnant women, and gynecological procedure station. Twenty marks were allocated for each station giving a total score of 80. The OSCE scores for study group were compared with those of the control group using Student's t-test; p < 0.05 was considered statistically significant. RESULTS: The total mean OSCE score was statistically significantly higher in the study group (62.36 vs. 47.94, p < 0.001). The study group participants showed significantly higher scores in the gynecological procedure station (16.74 vs. 11.62, p < 0.0001) and obstetric examination station (16.72 vs. 10.79, p < 0.0001). CONCLUSION: Clinical teaching at outpatient settings leads to an improvement in students' performance in OSCE. There is evidence of remarkable improvement in the mastery of clinical skills as manifested in the students' scores in physical examination and procedures stations. These results will encourage us to have clinical teaching in other disciplines at outpatient settings.